2011
DOI: 10.1021/ja108211m
|View full text |Cite
|
Sign up to set email alerts
|

Development of Proneurogenic, Neuroprotective Small Molecules

Abstract: Degeneration of the hippocampus is associated with Alzheimer’s disease, and occurs very early in the progression of the disease. Current options for treating the cognitive symptoms associated with Alzheimer’s are inadequate, giving urgency to the search for novel therapeutic strategies. Pharmacologic agents that safely enhance hippocampal neurogenesis may provide new therapeutic approaches. We discovered the first synthetic molecule, named P7C3, which protects newborn neurons from apopotic cell death, and thus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
110
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 152 publications
(126 citation statements)
references
References 49 publications
1
110
0
Order By: Relevance
“…Developing pharmacological strategies for selectively increasing adult neurogenesis remains a goal of the pharmaceutical industry; some initial success has been reported (Pieper et al 2010) and this lead compound is currently being refined (MacMillan et al 2011). , or lacking NR2B subunits in abGCs (Kheirbek et al 2012a) all perform worse than controls.…”
Section: Abgcs and Pattern Separationmentioning
confidence: 99%
“…Developing pharmacological strategies for selectively increasing adult neurogenesis remains a goal of the pharmaceutical industry; some initial success has been reported (Pieper et al 2010) and this lead compound is currently being refined (MacMillan et al 2011). , or lacking NR2B subunits in abGCs (Kheirbek et al 2012a) all perform worse than controls.…”
Section: Abgcs and Pattern Separationmentioning
confidence: 99%
“…1). This analog displays a more favorable toxicity profile than P7C3, with no hERG channel binding, histamine receptor binding, or toxicity to HeLa cells (2,4,5). We have also found that Dimebon, an antihistaminergic drug long deployed in Russia that is claimed to have anti-apoptotic and mitochondrial protective properties (6, 7), displays modest efficacy in the same biologic assays used to discover and characterize P7C3 and P7C3A20 (2).…”
mentioning
confidence: 99%
“…edu, joseph.ready@utsouthwestern.edu, or andrew-pieper@uiowa.edu. receptor binding, or toxicity to HeLa cells (13,15,16). We have also found that Dimebon, an antihistaminergic drug that is reported to have anti-apoptotic and mitochondrial protective properties (17,18), displays modest efficacy in the same biologic assays used to discover and characterize P7C3 and P7C3A20.…”
mentioning
confidence: 99%